PENGGUNAAN MEDIA MADING UNTUK MENDUKUNG PEMBELAJARAN LITERASI BACA TULIS PADA MATERI TEKS BERITA - Elna Jaililun Misfaida; Muhammad Hambali (Universitas Negeri Makassar, 2023)
The purpose of this study was to find out and analyze the use of wall magazines in the learning process of literacy in class VIII students of SMPN 3 Montong Tuban. The type of research used Qualitative research is descriptive research with interviews as a research instrument that involves 13 class VIII students as relevant informants, which is a class with an independent curriculum and low literacy quality. This study shows that the 13 students think that literacy magazines help learning to increase literacy become easier and more enjoyable. Overall, the learning media